Buyang Huanwu decoction promotes angiogenesis and improves hemorheological parameters after cervical spinal cord injury - Luchun Xu; Yongdong Yang; Guozheng Jiang; Yushan Gao; Jiawei Song; Yukun Ma; Jiaojiao Fan; Guanlong Wang; Xing Yu; Xiangsheng Tang (Journal of Traditional Chinese Medical Sciences)
Objective: To explore the effects of Buyang Huanwu decoction (BYHWD) on vascular neogenesis and hemorheological parameters following cervical spinal cord injury (SCI). Methods: An acute cervical SCI model was established using 84 female Sprague–Dawley rats. Functional recovery of the rats was evaluated using the forelimb locomotor scale score, forelimb grip strength test, and Basso-Beattie-Bresnahan score. The animals were subsequently euthanized at days 7 and 28 postoperatively. The gross morphology, neuronal survival, and myelin sheath in the injured area were evaluated using hematoxylin and eosin (HE), Nissl, and luxol fast blue (LFB) staining, respectively. Immunofluorescence staining was used to observe CD31 expression 7 days post-injury. Furthermore, the expression of CD31, neuronal nuclear protein (NeuN), and myelin basic protein (MBP) were evaluated 28 days post-injury. Additionally, vascular endothelial growth factor A (VEGFA) and VEGF receptor-2 (VEGFR-2) expression was evaluated using western blotting. Whole-blood viscosity, plasma viscosity, and red blood cell aggregation were measured using a hemorheometer. Results: From postoperative days 3–28, motor function in the BYHWD group began to recover considerably compared to the SCI group. BYHWD effectively restored spinal cord histopathology. In addition, the number of NeuN-positive cells, and fluorescence intensity of CD31at 7 and 28 days and MBP significantly increased in the BYHWD group compared with the SCI group (all P < .05). Moreover, this decoction significantly upregulated the expression of VEGFA and VEGFR-2 (all P < .05). BYHWD improved the hemorheology results (i.e., except erythrocyte aggregation index in the low-dose group), revealing statistically significant differences compared with the SCI group (all P < .05). Conclusion: BYHWD effectively promoted angiogenesis, improved hemorheological parameters, and protected neurons and myelin sheaths, ultimately promoting the recovery of neurological function after cervical SCI in rats. These findings suggest that BYHWD promotes vascular neogenesis through the VEGFA/VEGFR-2 pathway.